Revisiting the role of woman pastors in the church in Tshwane - Wagner-Ferreira, Elizabeth C. (HTS teologiese studies, 2011)
The purpose of this article was to obtain feedback from women pastors in and around the Tshwane metropole in South Africa on their experiences of their role as pastors. The question at stake was: are woman pastors more often approached for counselling? Therefore, half structured interviews were conducted in order to explore their life stories. The four core tasks of practical theological interpretation, according to Richard Osmer, were used as the framework for this article.